Retrospective Study for Assessing Outcomes and Cost-Effectiveness in Open versus Laparoscopic Appendectomy - Haque, Mohammad Anamul (Med Phoenix, 2025)
Introduction: Acute appendicitis is one of the most common causes of acute abdominal pain. Both open appendectomy (OA) and laparoscopic appendectomy (LA) are widely performed; however, their relative outcomes remain debated, particularly in low-resource countries.Materials and methods: This retrospective cohort study included 265 patients who underwent appendectomy between March 2023 and November 2024 at Narayani Central Hospital, Birgunj. Of these, 193 underwent OA and 72 underwent LA. Patients with conversion laparotomy, primary laparotomy, stump appendicitis, or pregnancy were excluded. Demographic data, operative time, hospital stay, cost, and complications were analyzed. Categorical variables were compared using the Chi-square or Fisher’s exact test, and continuous variables were analyzed using the Mann–Whitney U test.Results: Most patients were aged 10–19 years, with a male predominance (63%). The overall complication rate was significantly lower in the LA group than in the OA group (2.78% vs. 19.17%, p = 0.0008). The mean operative time was longer for LA (80.5 ± 21.9 min) than for OA (34.4 ± 11.8 min, p < 0.05). Median hospital stay was slightly shorter in the LA group (2.06 ± 0.29 days) than in the OA group (2.09 ± 0.42 days, p < 0.05). Mean hospital cost was higher for LA (NPR 42,819 ± 1,400) than for OA (NPR 41,981 ± 3,156, p < 0.05). Both the Hasson and Veress needle techniques were safe for pneumoperitoneum creation, with no port-site injuries reported.Conclusion: Laparoscopic appendectomy is associated with fewer complications, a shorter hospital stay, and better cosmetic outcomes compared with open appendectomy, though it requires longer operative time and slightly higher cost. In low-HDI settings, OA remains a practical alternative; however, LA should be encouraged where surgical expertise and resources are available.